2001
DOI: 10.1109/70.964670
|View full text |Cite
|
Sign up to set email alerts
|

Automatic decomposition of planned assembly sequences into skill primitives

Abstract: This paper presents a new method to decompose complex sequences of assembly operations into skill primitives. This can be realized by analyzing hyperarcs of the underlying AND/ORgraphs representing automatically generated assembly plans. Features like local depart spaces, symbolic spatial relations, and the necessary tools classify the type of assembly operation (peg in hole, placements, alignments, etc.). Skill primitives are robot movements or commands for grippers and tools. The unified modeling language (U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(29 citation statements)
references
References 35 publications
(45 reference statements)
0
29
0
Order By: Relevance
“…an assembly sequence results from systematically disassembling the final product and reversing the disassembling sequence (Lee, 1989;Mosemann and Wahl, 2001). This recursive decomposition process may be represented by the non-ordered directed tree, which is called ''assembly tree''.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…an assembly sequence results from systematically disassembling the final product and reversing the disassembling sequence (Lee, 1989;Mosemann and Wahl, 2001). This recursive decomposition process may be represented by the non-ordered directed tree, which is called ''assembly tree''.…”
Section: Related Workmentioning
confidence: 99%
“…It usually employs the contact-base feature or mating relations to represent the precedence relationships of the product. Mosemann and Wahl suggested that the assembly precedence could be formulated by using the skill primitives classified by the decomposition (Mosemann and Wahl, 2001). The limitation of many of these approaches is that they only consider partial assembly characteristics of a product to determine precedence constraints and sequences (Rajan and Nof, 1996).…”
Section: Related Workmentioning
confidence: 99%
“…A knowledge based system was used to generate assembly sequence in tree form from CAD design data and forward chaining inference for generating task level commands. Mosemann and Wahl [14] used AND/OR graphs for sequence representation and by analyzing algorithmically hyperarcs of graphs, complex sequences of assembly operations were decomposed into skill primitives. Unified modeling language (UML) was used to model robot tasks and skill primitives.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…(2000), Hasegawa etc. (2000), Chen et al (1999), Hert and Lumelsky (1999), Egerstedt and Hu (2002), Mosemann and Wahl (2001), to name a few. All these algorithms are not suitable to our cleaning robot applications.…”
Section: Introductionmentioning
confidence: 99%